2016
DOI: 10.1177/2167702616658634
|View full text |Cite
|
Sign up to set email alerts
|

Social Acknowledgment of Violent Experiences and Its Role in PTSD and Appetitive Aggression Among High-Risk Males in South Africa

Abstract: Violence exposure poses a risk for posttraumatic stress disorder (PTSD) and appetitive aggression. Does acknowledgment of violent experiences by one’s social environment also affect these adverse consequences of violence? We investigated relations between number of traumatic event types, number of violent offenses, PTSD symptoms, appetitive aggression, and social acknowledgment. A total of 290 participants were recruited through a Cape Town rehabilitation center for offenders. Using path analysis, we demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 46 publications
4
18
0
1
Order By: Relevance
“…Recently – and in line with research demonstrating that social exclusion and rejection are associated with aggressive behaviour (DeWall, Twenge, Gitter, & Baumeister, 2009; Twenge, Baumeister, Tice, & Stucke, 2001) – Sommer et al (2017b) found a positive association between general disapproval and appetitive aggression, a type of aggression which is perceived as self-rewarding rather than reactive (Elbert, Moran, & Schauer, 2017) and thus potentially fuels the cycle of violence in already violent environments such as low-income communities in South Africa. In contrast, recognition and family disapproval were found to be unrelated to appetitive aggression.…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…Recently – and in line with research demonstrating that social exclusion and rejection are associated with aggressive behaviour (DeWall, Twenge, Gitter, & Baumeister, 2009; Twenge, Baumeister, Tice, & Stucke, 2001) – Sommer et al (2017b) found a positive association between general disapproval and appetitive aggression, a type of aggression which is perceived as self-rewarding rather than reactive (Elbert, Moran, & Schauer, 2017) and thus potentially fuels the cycle of violence in already violent environments such as low-income communities in South Africa. In contrast, recognition and family disapproval were found to be unrelated to appetitive aggression.…”
Section: Introductionsupporting
confidence: 57%
“…surroundings with many potential traumatic events) could be a breeding ground for appetitive aggression, as confirmed by a positive association between traumatic events and appetitive aggression (Sommer et al, 2017b). Furthermore, as violence perpetration increases, aggression may be perceived more positively (Sommer et al, 2017b; Köbach et al, 2015; Weierstall et al, 2013).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations